2008
DOI: 10.5194/hess-12-393-2008
|View full text |Cite
|
Sign up to set email alerts
|

Winter climate affects long-term trends in stream water nitrate in acid-sensitive catchments in southern Norway

Abstract: Abstract. Controls of stream water NO 3 in mountainous and forested catchments are not thoroughly understood. Longterm trends in stream water NO 3 are positive, neutral and negative, often apparently independent of trends in N deposition. Here, time series of NO 3 in four small acid-sensitive catchments in southern Norway were analysed in order to identify likely drivers of long-term changes in NO 3 . In two sites, stream water NO 3 export declined ca 50% over a period of 25 years while in the other sites NO 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The seven natural catchments in Norway are part of the national program for monitoring effects of long-range transported air pollution (Garmo & Skancke, 2018). Monitoring started during the early 1970s in four stations (de Wit, Hindar, & Hole, 2008), and around 1990 in three other stations. The catchments are all located on acid-sensitive bedrock and land cover varies from forest, forest interspersed with peatland, and predominantly tundra or bare rock.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The seven natural catchments in Norway are part of the national program for monitoring effects of long-range transported air pollution (Garmo & Skancke, 2018). Monitoring started during the early 1970s in four stations (de Wit, Hindar, & Hole, 2008), and around 1990 in three other stations. The catchments are all located on acid-sensitive bedrock and land cover varies from forest, forest interspersed with peatland, and predominantly tundra or bare rock.…”
Section: Methodsmentioning
confidence: 99%
“…Declines in NO 3 concentrations in natural catchments dominated over change in totN. In natural catchments, most totN consists of organic N and the dynamics of organic N are closely linked to those of DOM, which is usually elevated during the summer and autumn (Lepisto, Kortelainen, & Mattsson, 2008) whereas NO 3 is highest during the dormant season (de Wit et al, 2008) and likely to be more strongly linked to atmospheric deposition (Vuorenmaa et al, 2018).…”
Section: Changes In Fertilizer Application Explained Downward Totn Trmentioning
confidence: 99%
See 2 more Smart Citations
“…is a trend of increasing nitrate export in surface waters that has been observed in many alpine and high-elevation catchments, such as those in the Colorado Rocky Mountains, USA , the Alps of northern Italy (Rogora, 2007), and southern Norway (de Wit et al, 2008), for which the process-level controls are just beginning to be explored. suggested that observed increases in nitrate export from the high-elevation Loch Vale catchment in the Colorado Front Range were the result of warmer temperatures that are melting ice in glaciers and rock glaciers.…”
Section: N Mladenov Et Al: Atmospheric Deposition As a Source Of Camentioning
confidence: 99%